2000
DOI: 10.1159/000016614
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Mineral Distributions in Dentine Lesions and Subsequent Remineralization in vitro

Abstract: Though the mineral distribution of the dentine carious lesion varies largely from tooth to tooth and from patient to patient, there are two main distribution profiles that characterize natural carious lesions in dentine. These profiles include softened and subsurface lesion types. The mineral distribution relationship between the starting profile and the profile after remineralization is not known. In order to study the relational aspects, we have produced demineralized dentine samples in vitro with mineral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
61
1
13

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 18 publications
9
61
1
13
Order By: Relevance
“…Arends et al, 1990]. Also, Kawasaki et al [2000] showed an effect of fluoride on remineralization of shallow (!165 Ìm) dentinal lesions with various mineral distributions. With an in situ model Nyvad et al [1997] showed -in comparison with non-treatment -that daily plaque removal and application of 2% NaF could inhibit progression and even result in partial remineralization of dentinal lesions Intra-oral fluoride levels between 0.04 and 0.1 ppm may be found in saliva and plaque fluid when a fluoride toothpaste or rinse is being used [Duckworth and Morgan, 1991;Leverett et al, 1993].…”
Section: Discussionmentioning
confidence: 93%
“…Arends et al, 1990]. Also, Kawasaki et al [2000] showed an effect of fluoride on remineralization of shallow (!165 Ìm) dentinal lesions with various mineral distributions. With an in situ model Nyvad et al [1997] showed -in comparison with non-treatment -that daily plaque removal and application of 2% NaF could inhibit progression and even result in partial remineralization of dentinal lesions Intra-oral fluoride levels between 0.04 and 0.1 ppm may be found in saliva and plaque fluid when a fluoride toothpaste or rinse is being used [Duckworth and Morgan, 1991;Leverett et al, 1993].…”
Section: Discussionmentioning
confidence: 93%
“…1, formulation C, 14 days; data not quantified). This would allow only partial remineralisation, as observed for carious dentine remineralisation, with high mineral concentration on the surface layer preventing mineral diffusion to the subsurface [Kawasaki et al, 2000]. Accelerating the in vitro remineralisation time and allowing complete remineralisation may be an initial goal when developing products intending to prevent or reduce erosion progression in dentine.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that the kind of lesion influences the behavior to further de-or remineralization, as the surface layer, porosity and lesion depth can play an important role in the mineral diffusion [ten Cate, 1994;Kawasaki et al, 2000;Preston et al, 2008;Bertassoni et al, 2010].…”
mentioning
confidence: 99%